Case report: Cytokine therapy and an intracoronary autologous bone marrow-derived cell infusion with Impella support in a patient with dilated cardiomyopathy and a severely reduced ejection fraction - Hall, Russell Charles; Ramaseshan, Rohini; Reid, Alice; Jones, Daniel A.; Mathur, Anthony (Frontiers in Cardiovascular Medicine, 2022)
INTRODUCTION This is the first reported case of a patient with dilated cardiomyopathy (DCM) and a severely impaired left ventricular function to receive a combined treatment of granulocyte colony-stimulating factor therapy and an intracoronary delivery of autologous bone marrow-derived mononuclear cells with percutaneous circulatory assistance (the Impella CP device; Abiomed, Danvers, MA). MAIN SYMPTOMS & OUTCOME Three months post-treatment the gentleman in his early 70s demonstrated an improvement in left ventricular ejection fraction (13% to 17%) and a reduction in New York Heart Association class from III to class I. There was also an improvement in his 6-minute walk test (147 metres to 357 metres), N-terminal pro-brain natriuretic peptide level (14,099 ng/l to 7,129 ng/l) and quality of life scores. There were no safety concerns during the treatment or follow-up. CONCLUSION This case report suggests combined cell and cytokine therapy with adjunctive circulatory support could be a safe and promising treatment for patients with DCM and a severely reduced ejection fraction.